Peptide-Directed Photo-Cross-Linking for Site-Specific Conjugation of IgG - Park, Jisoo; Lee, Yumi; Ko, Byoung Joon; Yoo, Tae Hyeon (Bioconjugate Chemistry, 2018)
Conjugation of antibody has expanded its applications in therapeutics and diagnostics, and various methods have been developed based on chemical or enzymatic reactions. However, the majority of them have focused on synthetic molecules such as small molecules, nucleic acids, or synthetic materials, but site-specific conjugation of antibody with protein cargo has rarely been demonstrated. In this Communication, we report a PEptide-DIrected Photo-cross-linking (PEDIP) reaction for site-specific conjugation of IgG with protein using an Fc-binding peptide and a photoreactive amino acid analogue, and demonstrate this method by developing an immunotoxin composed of a Her2-targeting IgG (trastuzumab) and an engineered Pseudomonas exotoxin A (PE24). The ADP-ribosylation of eukaryotic elongation factor-2 by the bacterial toxin inhibits the ribosomal translation of protein, and the trastuzumab-PE24 conjugate exhibited the cytotoxicity toward Her2-overexpressing cell lines. The PEDIP reaction can also be applied for many other types of cargo with slight modifications of the method.
Keywords: Crosslinking reaction; Enzymatic reaction; ITS applications; Photo-cross-linkings; Site-specific; Small molecules; Specific conjugations; Synthetic materials; Synthetic molecules; Trastuzumab; ADP Ribose Transferases; Bacterial Toxins; Cell Line, Tumor; Chromatography, Gel; Cross-Linking Reagents; Electrophoresis, Polyacrylamide Gel; Exotoxins; Humans; Immunoglobulin G; Immunotoxins; Peptides; Photochemical Processes; Trastuzumab; Virulence Factors